2019
DOI: 10.1208/s12248-019-0355-5
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Delphinidin Prevents Neoplastic Transformation of Mouse Skin JB6 P+ Cells: Epigenetic Re-activation of Nrf2-ARE Pathway

Abstract: Redox imbalance is a major contributor to the pathogenesis of melanoma and nonmelanoma skin cancer. Activation of the nuclear factor E2-related factor 2 (Nrf2)-antioxidant responsive element (ARE) pathway is an intrinsic defense mechanism against oxidative stress. Flavonoids such as anthocyanidins, which are found abundantly in fruits and vegetables, have been shown to activate Nrf2. However, the epigenetic and genetic mechanisms by which anthocyanidins modulate the Nrf2-ARE pathway remain poorly understood in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 57 publications
1
31
0
Order By: Relevance
“…However, hOBs exposed to MBE were not observed to activate ROS or nitrotyrosine production, suggesting MBE, as an antioxidant, can activate the expression of Nrf2. This result is consistent with another study which showed that delphinidin can activate Nrf2 as an epigenetic demethylating agent of the Nrf2 promoter (Kuo et al, 2019[ 24 ]). We exposed MBE and CSE to hOBs in three incubation modes including pre-incubation, co-incubation and post-incubation as described.…”
Section: Discussionsupporting
confidence: 92%
“…However, hOBs exposed to MBE were not observed to activate ROS or nitrotyrosine production, suggesting MBE, as an antioxidant, can activate the expression of Nrf2. This result is consistent with another study which showed that delphinidin can activate Nrf2 as an epigenetic demethylating agent of the Nrf2 promoter (Kuo et al, 2019[ 24 ]). We exposed MBE and CSE to hOBs in three incubation modes including pre-incubation, co-incubation and post-incubation as described.…”
Section: Discussionsupporting
confidence: 92%
“…They have an antioxidant activity which is associated with the diorthohydroxyl functional moiety. Among various kinds of anthocyanins, delphinidin (Dp) has attracted much attention due to its largest number of hydroxyl groups on the B ring and high antioxidant activity [ 30 , 31 ]. In this study, the HepG2 cells, which possessed many biological characteristics of hepatocytes and the activity of many phases I and II antioxidant enzymes, were selected to evaluate the antioxidative property effect of delphinidin treatment [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, that is because heme-derived metabolites produced by HO-1 have powerful antioxidant and cytoprotective activities [ 46 , 47 ]. In addition, according to the related researches, it has been found that HO-1 and NQO1 could be effectively activated by Nrf2 [ 30 ]. In our study, delphinidin treatment significantly upregulated the protein expression of Nrf2 and HO-1 ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The anthocyanidin decreased the CpG methylation ratio at the Nfe2l2 promoter resulting in upregulated mRNA and protein expression levels of Nrf2 and its target genes. The study further demonstrated downregulation of Dnmts (Dnmt1a and Dnmt3a), and class I and II Hdacs linked to reactivation of the Nrf2 pathway in JB6 P+ cells [84].…”
Section: Delphinidinmentioning
confidence: 69%